2014
DOI: 10.1016/j.marchem.2014.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recirculation of seawater enriched in inorganic nitrogen on dissolved organic carbon processing in sandy seepage face sediments

Abstract: Please cite this article as: Ibánhez, J. Severino P., Rocha, Carlos, Effects of recirculation of seawater enriched in inorganic nitrogen on dissolved organic carbon processing in sandy seepage face sediments, Marine Chemistry (2014Chemistry ( ), doi: 10.1016Chemistry ( /j.marchem.2014 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 51 publications
7
12
0
Order By: Relevance
“…Relevant sediment properties during the field sampling campaigns performed during December 2009 and April 2010 showed high similarity to those presented in Rocha et al () and Ibánhez and Rocha () for previous work at the site (including those reported for October 2010 and January 2011 when the experimental work presented here was performed). Sediment porosity at the seepage face (Stations A and B) was characterized by low temporal variability (Supporting Information Fig.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Relevant sediment properties during the field sampling campaigns performed during December 2009 and April 2010 showed high similarity to those presented in Rocha et al () and Ibánhez and Rocha () for previous work at the site (including those reported for October 2010 and January 2011 when the experimental work presented here was performed). Sediment porosity at the seepage face (Stations A and B) was characterized by low temporal variability (Supporting Information Fig.…”
Section: Resultssupporting
confidence: 85%
“…Those findings together with the vertical distribution of aerobic respiration rates and the absence of substantial seasonal difference among both experimental periods suggest that at the highest imposed seepage rates and under O 2 saturated porewater, aerobic heterotrophic processes are ultimately constrained by OM availability and quality at the seepage face. Low standing stocks of OM within the sediment (Rocha et al ; Ibánhez and Rocha ; Supporting Information Fig. 1) together with the measured aerobic respiration rates suggest the fast turnover of OM within the seepage face sediment.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Due to the high mobility of N compounds in the environment and the role N plays in microbial and primary producer metabolism, anthropogenic N enrichment of STEs could also promote alterations on the cycling of other elements such as C. Hence, mobilization of organic C from high residence time reservoirs like peat bogs (Bragazza et al, 2006), the Artic tundra (Mack et al, 2004), or alpine steppes (Chen et al, 2020) is increasingly linked to the enhancement of microbial and enzymatic activity caused by anthropogenic N enrichment. Nevertheless, to our knowledge, the effect of N enrichment on the transformation of organic matter in STEs has only been explored to date in incubation experiments (Ibánhez and Rocha, 2014a). In this study, we use an extensive field dataset collected in an STE seepage face to explore the effects of changing N enrichment within the STE over the quantity and quality of the fluorescent dissolved organic matter (FDOM).…”
Section: Introductionmentioning
confidence: 99%